Muslim Style in South India - Caroline Osella and Filippo Osella (Fashion Theory, Volume 11, Issue 2/3, pp. 1-20, 2007)
This article presents ethnographic material from contemporary Kerala, where recent shifts in Muslim women's dress styles (shift from sari towards salwaar kameez; adoption of pardah; use of Arabic abaya) have come under critique. We show that commentators fail to take into account the degree to which all Indian women-not simply Muslims- are heavily constrained in dress by issues of modesty and "decency." Dress codes for all communities and both sexes have been continually reworked since the nineteenth century. Muslims' recent changes are prompted by a shift away from Hindu idioms and towards more Islamic idioms of modesty; changes index Indian Muslims' growing realization (also apparent in other spheres) that much of India's putatively commonculture is actually rooted in Hindu practice. We also show that while popular and ethnographic focus alike falls upon women, men are also deeply caught up in respecting dress codes. But concerns with decency are always negotiated within desires for fashion. Kerala's Muslim community is more than averagely high spending and Muslims are especially interested in dressing well and participating in worlds of fashion, which may be vernacular ishtyle (Indian film driven) or global brands